1984
DOI: 10.1007/bf01887839
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty in diagnosing hemobilia from a hepatic artery aneurysm: Value of endoscopic retrograde cholangiography

Abstract: A case of hemobilia due to a hepatic artery aneurysm is described. Despite 2 arteriograms and 2 laparotomies, the cause of the bleeding remained undetected until a further selective cannulation of the celiac axis artery was performed. Endoscopic retrograde cholangiography demonstrated that postoperative jaundice was not due to obstruction and outlined the aneurysm within a hepatic duct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Angiography may provide a clue at times, however, the use of angiography does not always lead to the correct diagnosis. 13 There are various treatment modalities available for these patients as hepatic resection, arterial ligature, and vascular embolization. 6 Angiographic occlusion of the vascular lesion by embolization or by endovascular placement of Gianturco's coils is being used more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Angiography may provide a clue at times, however, the use of angiography does not always lead to the correct diagnosis. 13 There are various treatment modalities available for these patients as hepatic resection, arterial ligature, and vascular embolization. 6 Angiographic occlusion of the vascular lesion by embolization or by endovascular placement of Gianturco's coils is being used more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that the extravasated contrast continued to rapidly disappear despite ongoing infusion, in conjunction with the symptoms of diaphoresis and flushing (typical of contrast being injected into the vascular space) confirmed our findings of an hepatic artery aneurysmbiliary tract fistula. Only two other reports [4,34] have suggested that ERC played a critical role in the diagnosis of the aneurysm. In both cases, although ERC findings suggested the lesion, the actual aneurysm was not delineated.…”
Section: Discussionmentioning
confidence: 99%